MENCARI ILMU MENURUT PANDANGAN AGAMA ISLAM DAN MANIFESTASINYA DALAM NASKAH RADEN SULAM - Zianna Fasichalisna (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Education is crucial in life. Therefore it is mandatory for everyone to seek knowledge. It will be discussed about seeking knowledge according to the islamic religious view and its manifestations in the Raden Sulam manuscript. Raden Sulam's script tells the story of the development of Islam through the point of view of Raden Sulam who broadcasts the religion. In this article, there are two formulations of the problem, namely (1) How to seek knowledge according to the Islamic view? (2) What is the form of knowledge-seeking behavior in the Raden Sulam manuscript? The method used in the research is a descriptive qualitative research method, with the theory used, namely the genetic structuralism approach. The approach of genetic structuralism is considered to be able to assist researchers in analyzing the content of manuscripts and relating them to the state of affairs in society. The result of this research is that, in Islam, seeking knowledge must fulfill several things, namely having awareness, having enthusiasm, carrying out tirakat, and also practicing what has been learned to the community. Raden Sulam in the script has carried out these four things. He has had the awareness to learn, has a strong spirit, carries out tirakat in the process of seeking knowledge, and then broadcasts the religion of Islam to the kings. In seeking knowledge Raden Sulam has fulfilled part of the islamic religious view of seeking knowledge.